The Effect of Ladder Drill Exercise on Increasing Extracurricular Student Agility at SMKN 1 Bengkulu City - Defliyanto; Panji Pangestu (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
This study aims to determine the effect of Ladder drill training on increasing the agility of extracurricular students at SMK Negeri 1 Bengkulu City. This study used a quasi-experimental method with a One group pretest-posttest design where in this study there was no comparison group. The population of this study were all students who took part in extracurricular volleyball and futsal, totaling 32 students. The instrument used is a test and measurement using the Illinois run agility test. The test results show that there is an effect of the Ladder drill training method on increasing agility. Hypothesis test shows the value of t count 22.4 > t table 1.694.